Design and Development of a Decision Support Package for Low Back Pain - Patel, Shilpa (Blackwell Publishing Ltd, 2014)
OBJECTIVE: To develop a decision support package for people with low back pain (LBP) referred for physiotherapy. METHODS: We used a program of exploratory work, including literature reviews, a Delphi study, a nominal group with physiotherapists, focus groups with patients, and secondary analysis of existing interview data. RESULTS: We developed an information booklet describing the evidence-based treatment modalities available in a physiotherapy department. This includes data on likely benefits and risks and how the intervention is delivered. The booklet specifically addresses questions identified as important in our exploratory work. Space is provided for patients to note down the pros and cons of each treatment and what matters to them when choosing treatments. The patient is subsequently directed to a section that explores any gaps in knowledge, values, support, and choice before finally clarifying if a treatment decision is possible. At this stage they are encouraged to note down any questions or concerns they have to be discussed at the first physiotherapy consultation. This overall package includes patient material in the form of a booklet posted prior to their consultation, plus the enhanced consultation with the specially trained physiotherapist. Patients then receive their chosen treatment. In addition we developed a training package for physiotherapists that explains the content of the booklet and supports them in using informed, shared decision making in their consultation. CONCLUSION: This package has the potential to improve effectiveness of treatments and patient satisfaction for LBP by facilitating patient choice and therefore matching patients more effectively to different treatments.